2022
DOI: 10.2147/idr.s367460
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Phage-Mediated Inhibition and Removal of Multidrug-Resistant Pseudomonas aeruginosa Biofilm on Medical Implants

Abstract: Purpose Despite the growing interest in bacteriophage (phage) usage for the prevention, control, and removal of bacterial biofilms, few scientific data exist on phage applications on medical implant surfaces, while none exists on multiple implants. In this study, we aimed to isolate, biophysically characterize and assess phages as potential antibiofilm agents to inhibit and remove multidrug-resistant (MDR) Pseudomonas aeruginosa biofilm on catheter and endotracheal tube … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…However, some studies have shown that the studied phages retain their initial titer of viral particles only at pH 7.0–8.0 [ 66 ] and that the virions of the studied bacteriophages do not withstand extreme pH levels (2.0 and 12.0) [ 67 ]. Thus, in studies of the biological properties of lytic myophage MJ1 against multiresistant strains of E.coli, it was found that this bacteriophage had maximum stability at pH 7 and was also relatively stable at pH 5 and 9.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have shown that the studied phages retain their initial titer of viral particles only at pH 7.0–8.0 [ 66 ] and that the virions of the studied bacteriophages do not withstand extreme pH levels (2.0 and 12.0) [ 67 ]. Thus, in studies of the biological properties of lytic myophage MJ1 against multiresistant strains of E.coli, it was found that this bacteriophage had maximum stability at pH 7 and was also relatively stable at pH 5 and 9.…”
Section: Discussionmentioning
confidence: 99%
“…The host range of propagated phages were tested for phage activity following the standard spot test procedure described earlier 18 against E. coli strains and other non- E. coli bacteria. One hundred μL of each of the host cells at log phase were added to 5 mL of sterile molten soft agar (0.8%) and poured over a previously prepared Nutrient Agar plate surface.…”
Section: Methodsmentioning
confidence: 99%
“…In Table 2 are summarized some studies found in the literature regarding bio-inspired antimicrobial coatings [ 115 , 116 ].…”
Section: Modern Technological Advances In Antimicrobial Coatings For ...mentioning
confidence: 99%